Longitudinal scRNA-seq of retinal organoids derived from Stargardt disease patient with ABCA4 mutation - Yingke Zhao; Yun Cheng; Ting Li; Jiawen Wu; Chenchen Li; Shenghai Zhang; Jihong Wu (Scientific Data)
Abstract Stargardt disease (STGD), predominantly caused by mutations in the ABCA4 gene, is a leading cause of inherited retinal degeneration. Although several lines of mice expressing disease-causing variants have been produced, mice due to the lack of macular may not be the perfect model to mimic the characteristics of STGD. To address this knowledge gap, we generated retinal organoids from patient-derived induced pluripotent stem cells (iPSCs) harboring ABCA4 mutations and performed biological validation. The generated retinal organoids were subjected to single-cell RNA sequencing (scRNA-seq) at major developmental stages (40, 90, 150, 200, and 260 days), and we additionally compared the transcriptomics with our recently published control retinal organoids to further confirm the reliability of the dataset. By using iPSCs carrying most common variant in Chinese STGD patients, the dataset not only provides a powerful resource for studying STGD, but also offers novels insight into the developmental mechanisms underlying ABCA4-associated pathological changes in the retinal organoid system.